Do Heterodox Theories Have Anything in Common? A Post-Keynesian Point of View - Marc Lavoie (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2006)
The paper questions the wide-spread assertion that non-orthodox schools of thought in economics have only one thing in common – their rejection of mainstream (neoclassical) economics. The author shows by contrast that heterodox currents share some fundamental analytical insights. The paper focuses on a comparison of modern Marxist conceptions with those of Post-Keynesian economists, including the works of Kaleckians and Sraffians. This is shown by examining four fields: the issue of rationality (where the adjustment principle is explicitly accepted by important heterodox authors), price theory (with cost-plus pricing combined to some long-run adjustment), growth theory (where the Kaleckian model has been adopted by authors from all schools), and finally monetary theory (where authors from all backgrounds are successfully integrating real and monetary analysis by taking into account financial markets). The author concludes that mutual feedback between the various heterodox currents has been beneficial to all, despite an unavoidable hyper-specialisation.
Keywords: B5; 330